2000
DOI: 10.7589/0090-3558-36.2.378
|View full text |Cite
|
Sign up to set email alerts
|

Proliferative Pododermatitis Associated with Virus-like Particles in a Northern Gannet

Abstract: Small multifocal lesions of proliferative pododermatitis were observed in an emaciated adult male northern gannet (Morus bassanus). Ultrastructurally, these lesions were associated with numerous virus-like particles with a size and morphology suggestive of Papovaviridae. DNA in situ hybridization with probes for avian polyomaviral and papillomaviral nucleic acid and an immunohistochemical test for the presence of papillomaviral antigen failed to identify this virus further. To our knowledge, papovavirus-like p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 8 publications
2
3
0
1
Order By: Relevance
“…Groups of rounded, viral particles with a 35 nm in diameter were found intranuclearly in sections of ultrathin fragments, which confer the literature related to bovine (Tajima et al;Zhou et al;Jelinek &Tachezy, 2005;Maeda et al;Roperto et al), dogs (Buff et al, 1988), deer (Sundberg et al, 1985b), cats (Sundberg et al) and poultry (Daoust et al, 2000). Intracytoplasmic viral particles, cited by Jelineck & Tachezy (2005) in cattle and by Sundberg et al, in cats were not observed in this study, even the crystalline arrangements described by Elzein et al, in cattle and by Sundberg et al, (1985b) in deer.…”
Section: Discussionsupporting
confidence: 52%
“…Groups of rounded, viral particles with a 35 nm in diameter were found intranuclearly in sections of ultrathin fragments, which confer the literature related to bovine (Tajima et al;Zhou et al;Jelinek &Tachezy, 2005;Maeda et al;Roperto et al), dogs (Buff et al, 1988), deer (Sundberg et al, 1985b), cats (Sundberg et al) and poultry (Daoust et al, 2000). Intracytoplasmic viral particles, cited by Jelineck & Tachezy (2005) in cattle and by Sundberg et al, in cats were not observed in this study, even the crystalline arrangements described by Elzein et al, in cattle and by Sundberg et al, (1985b) in deer.…”
Section: Discussionsupporting
confidence: 52%
“…28,41 Previous evaluation of papillomatous lesions revealed some similarities to virus-induced papillomata of dogs and cats (N. Robert, personal communication, 2009), and thus papillomavirus involvement was suspected. 34 Supporting this hypothesis, virus-like particles were found in a Northern gannet (Morus bassanus) with proliferative pododermatitis 4 and in multiple waterfowl species with verrucous hyperkeratotic lesions. 44 Proliferative foot lesions caused by herpesviruses were found in macaws and cockatoos as well as in a duck with ulcerative foot lesions.…”
supporting
confidence: 50%
“…Three were biopsies of cauliflower-like papillomatous growths (4,19, and 54 years old), and one was collected at necropsy from a 4-year-old with fissures. Spherical intracytoplasmic inclusions (120-140 nm in diameter) were observed in occasional keratinocytes from 2 cases with papillomatous growths (4 and 54 years old).…”
Section: Transmission Electron Microscopymentioning
confidence: 99%
“…Parenteral antibiotics may be necessitated if the masses grow infected, but the underlying condition will persevere because of the environmental factors (Routh, 2000). The condition has been reported in other birds, including raptors, falcons, eagle, geese, owls, gannet, penguins (Rodriguez-Lainz et al, 1997;Müller et al, 2000;Poorbaghi et al, 2012;Parsad et al, 2010;Gentz, 1996;Daoust et al, 2000;Reidarson et al, 1999) To the author's lore this is the first report of bumblefoot associated with osteomyelitis in mute swan.…”
Section: Introductionmentioning
confidence: 83%